Is exclusive breastfeeding an option or a necessity in Africa? A pooled study using the deuterium oxide dose-to-mother technique - Mulol, Helen (J Public Health Afr, 2020)
Given the valuable health, development, and economic benefits of human milk Exclusive Breastfeeding (EBF) is recommended by the World Health Organisation for the first six months of an infant’s life. Many resource-limited regions in Africa do not line-up with these recommendations, therefore EBF promotion efforts on the continent need to be scaled up and monitored. This study explores the human milk intake volumes of 5 countries (Benin, Central African Republic, Morocco, South Africa and Tanzania) both at country level and in a pooled sample of children at 3 months (n= 355) and at 6 months (n=193). Mean human milk intake volumes in the pooled samples were 697.6 g/day at 3 months and 714.9 g/day at 6 months. EBF was determined both by maternal recall as well as using the deuterium oxide dose-to-mother technique, using two different cut-offs of non-milk oral intake. Comparison of these results showed substantial over-reporting of EBF by maternal recall, which suggests that actual rates of EBF are even lower than reported, thus highlighting the importance of scaling-up EBF promotion strategies.